Joomla! : 24-hour trainer - Kramer, Jen (Programmer to programmer, 2011)
Build a complete, functional, and useful Joomla! Web site with this book-and-DVD tutorial As one of the most downloaded open source content management systems on the market today, Joomla! allows you to build functional, interactive Web sites without having to know PHP or MySQL